Integration of Naqli (Revealed) Knowledge and Aqli (Rational) Knowledge in Postgraduate Courses for Open and Distance Learning - Nurkhamimi Zainuddin; Rozhan M. Idrus; Ahmad Farid Mohd Jamal (International Journal of Social Science and Humanity, 2024)
This study discusses the development process of integrated Naqli and Aqli postgraduate courses for open and distance learning (NAPCOD) at Universiti Sains Islam Malaysia (USIM). This is a qualitative study using literature review and document analysis methods by assessing and analyzing discussions in texts content and being translated in the form of narrative approach. The NAPCOD are designed by first identifying a set of four (4) fundamental levels of Naqli and Aqli knowledge integration. These fundamental levels are subsequently converted to NAPCOD development process. The outcomes of this integration emphasize on good characters within the framework of Naqli and Aqli integration.